Microbiological quality of raw and smoked corbicula fluminea from selected districts in Kelantan - Shahad, Mohd Sharazi (2020)
Corbicula fluminea (Asian Clam) or locally known as ‘etak’ among Kelantanese, is an edible freshwater bivalve found on the surface or buried in sand and mud in the shallow water of riverbeds. As a filter feeder’s, bivalves can cause bioaccumulation of hazardous organic matters, heavy metals, and microbes from the surrounding aquatic environment. This study aims to identify the current status for microbiological quality of raw and smoked Corbicula fluminea collected from several vendors in three districts in Kelantan from Jun to July 2020. A total of thirty samples were analysed for total plate count (TPC), total coliform count (TCC), faecal coliform count (FCC) and the presence of E. coli. All samples of raw Corbicula fluminea (100%) samples were found unsatisfactory for TPC, TCC, and FCC and 73.3% of the samples were positive for the presence of E. coli. About 60% of smoked Corbicula fluminea (n=15) were found unsatisfactory for TPC, TCC and FCC, and 46.7% showed the presence of E. coli. In conclusion, the microbiological quality of raw and smoked C. fluminea sold in Kota Bharu, Pasir Mas and Bachok is unsatisfactory and unsafe for consumption, and its safety remains doubtful.